Pengaruh Penanaman Nilai Pendidikan Islam dalam Keluarga terhadap Moral Remaja di Desa Pugul Kecamatan Riau Silip Kabupaten Bangka - Yulisma, Yulisma; Febrino, Febrino (LENTERNAL: Learning and Teaching Journal, 2023)
The problem with this study is that in Pugul village, there are parents who instill the value of Islamic education well in their children and produce good moral children, and there are also parents who produce bad moral children, and vice versa. The aim of this study is to find out how much influence the cultivation of Islamic educational values in the family has on the morality of adolescents in Pugul village, Bangka district. The research method used is quantitative. The process of taking data from two variables uses a closed lift with data analysis techniques using simple linear regression. The results of the research show that there is a significant influence of the cultivation of Islamic educational values in the family on the morality of adolescents in Pugul village, Bangka district. It was deduced with a calculated result of 26,973 with a rate sig. of 0,000, which means 0,000 is less than 0.05 (0,000 < 0.05), so Ha was accepted and Ho rejected. On the regression equation obtained, values a of 28,833 and b of 0,802 indicate that the value of the coefficient of regression is positive. The determination coefficient (R square) indicates a value of 0.415, which means that the cultivation of Islamic educational value in the family affects the morality of adolescents by 41.5%, while the remaining 58.5% is influenced by some other factors.